2008
DOI: 10.1039/b714594b
|View full text |Cite
|
Sign up to set email alerts
|

Digital microfluidics and delivery of molecular payloads with magnetic porous silicon chaperones

Abstract: Digital microfluidics involves the manipulation of molecules and materials in discrete packages. This paper reviews our work using amphiphilic magnetic microparticles constructed from porous silicon. An individual porous particle can be used to carry a nanomole or smaller quantities of a reagent, and assemblies of the particles can encapsulate and transport microliter droplets of liquid containing inorganic, organic, or biological molecules. The tracking and identification of each particle can be accomplished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 75 publications
0
32
0
Order By: Relevance
“…Oxidation produces a volume expansion (Si to SiO 2 ) that shrinks the pores, locking the payload in place. After [124] Trapping of a positively charged drug payload in a porous SiO 2 layer by ionic adsorption. Porous SiO 2 (oxidized porous Si) has a negative surface charge; molecules with positive charges will spontaneously adsorb to the inner pore walls and surface.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…Oxidation produces a volume expansion (Si to SiO 2 ) that shrinks the pores, locking the payload in place. After [124] Trapping of a positively charged drug payload in a porous SiO 2 layer by ionic adsorption. Porous SiO 2 (oxidized porous Si) has a negative surface charge; molecules with positive charges will spontaneously adsorb to the inner pore walls and surface.…”
Section: Summary and Prospectsmentioning
confidence: 99%
“…50 They also 10 used the same principle with magnetic porous silicon chaperones and demonstrated the transport of a range of precursors required for droplet based assays and a thermal cycling of a DNA duplex. 51 Whilst their main focus was on the transport of a droplet within another liquid they did demonstrate transport of a magnetic liquid marble through air. 51 Zhao et al studied liquid marbles in air created using hydrophobic Fe3C>4 nanoparticles and observed that a magnet could be used to clear part of the upper surface of the liquid marble of any particles, thus exposing the liquid.…”
mentioning
confidence: 99%
“…51 Whilst their main focus was on the transport of a droplet within another liquid they did demonstrate transport of a magnetic liquid marble through air. 51 Zhao et al studied liquid marbles in air created using hydrophobic Fe3C>4 nanoparticles and observed that a magnet could be used to clear part of the upper surface of the liquid marble of any particles, thus exposing the liquid. When the magnet was removed the particulate layer re-covered in a similar manner to the self-coating process described in section 3.3.…”
mentioning
confidence: 99%
“…33 Another example of hybrid magnetic bead/inert support particles is microporous silicon particles impregnated with the magnetic nanoparticles. 34 These particles are useful when the reaction chemistry in the droplet-based microfluidic system is reactive with the Fe 2 O 3 particles. The porous silicon particles are synthesized via electrochemical corrosion of a Si wafer with hydrofluoric acid.…”
Section: Composite Magnetic Particles For Use In Microfluidicsmentioning
confidence: 99%